Classical demands and informal supplies: Two key missing pieces of Mexico’s growth puzzle - Ize, Alain (Estudios Económicos de El Colegio de México, 2025)
Why did Mexico's growth declined so much after the economy opened up? And why so little growth despite so many exports? The narratives proposed to explain these puzzles miss two key pieces: classical demands and informal supplies. To grow faster, the country needs to focus not just on its export supply capacity but also on its capacity to grow domestically and enhance productivity by pulling in informal labor. In a globalized world, this requires developing export niches that generate sufficient domestic value and producing goods and services that are more innovative, more attractive and with more dynamic demands.